The role of motor and nutritional individuality in childhood obesity - Parízková, J (Collegium antropologicum, 2012)
Nutritional and motor individuality vary significantly among human subjects, and their mutal relationship is decisive for a desirable energy balance and turnover with regard to body composition, physical fitness level and health. Early establishment of optimal individualities, with regard to genetic, epigenetic and other factors which influence the organism early in life is desirable for a positive life-long health prognosis and life expectancy. Approaches for the evaluation of both nutritional and motor individualities have been elaborated as an important starting point for their positive development and eventual modification. This should aim to achieve not only prevention of diseases, but also to improve health prevention and achieving the status of "positive health".
Keywords: vývoj dítěte; dítě; motorické dovednosti; Motor Skills; Child Development; předškolní dítě; zdravotní stav; lidé; tělesná výkonnost; Obesity; Child Nutrition Disorders; Female; Health Status; Male; ženské pohlaví; Humans; Child; mužské pohlaví; Physical Fitness; obezita; nutriční poruchy u dětí; Child, Preschool